Extreme population inversion in the fragments formed by UV photoinduced S–H bond fission in 2-thiophenethiol. Issue 16 (8th April 2016) - Ingle, Rebecca A.; Karsili, Tolga N. V.; Dennis, Gregg J.; Staniforth, Michael; Stavros, Vasilios G.; Ashfold, Michael N. R.
Abstract : UV photoexcitation of 2-thiophenethiol results in S–H bond fission and a population inversion in the cofragments. Abstract : H atom loss following near ultraviolet photoexcitation of gas phase 2-thiophenethiol molecules has been studied experimentally, by photofragment translational spectroscopy (PTS) methods, and computationally, by ab initio electronic structure calculations. The long wavelength (277.5 ≥ λ phot ≥ 240 nm) PTS data are consistent with S–H bond fission after population of the first 1 πσ* state. The partner thiophenethiyl (R) radicals are formed predominantly in their first excited Ã 2 A′ state, but assignment of a weak signal attributable to H + R(X̃ 2 A′′) products allows determination of the S–H bond strength, D 0 = 27 800 ± 100 cm −1 and the Ã–X̃ state splitting in the thiophenethiyl radical (Δ E = 3580 ± 100 cm −1 ). The deduced population inversion between the Ã and X̃ states of the radical reflects the non-planar ground state geometry (wherein the S–H bond is directed near orthogonal to the ring plane) which, post-photoexcitation, is unable to planarise sufficiently prior to bond fission. This dictates that the dissociating molecules follow the adiabatic fragmentation pathway to electronically excited radical products. π* ← π absorption dominates at shorter excitation wavelengths. Coupling to the same 1 πσ* potential energy surface (PES) remains the dominant dissociation route, but a minor yield of H atoms attributable to a rival fragmentation pathway is identified. These products are deduced to arise via unimolecular decay following internal conversion to the ground (S0 ) state PES via a conical intersection accessed by intra-ring C–S bond extension. The measured translational energy disposal shows a more striking change once λ phot ≤ 220 nm. Once again, however, the dominant decay pathway is deduced to be S–H bond fission following coupling to the 1 πσ* PES but, in this case, many of the evolving molecules are deduced to have sufficiently near-planar geometries to allow passage through the conical intersection at extended S–H bond lengths and dissociation to ground (X̃) state radical products. The present data provide no definitive evidence that complete ring opening can compete with fast S–H bond fission following near UV photoexcitation of 2-thiophenethiol.